ANALISIS KEPATUHAN PETUGAS DALAM PENGGUNAAN ALAT PELINDUNG DIRI DI INSTALASI PEMELIHARAAN SARANA DAN PRASARANA RUMAH SAKIT AWAL BROS PANAM - Yuliana, Anastasya Shinta; Filda; Purnamasari, Devi (LPPM Universitas Awal Bros, 2022)
ABSTRACT The use of PPE is a compliance that must be obeyed by the installation officer for the maintenance of hospital facilities and infrastructure. At Awal Bros Panam Hospital, which has many facilities for medical and non-medical equipment, so that IPSRS officers are responsible for repairing damaged hospital infrastructure. This study aims to determine the compliance of officers in using PPE at IPSRS at Awal Bros Panam Hospital. This type of research is qualitative, and the research used a Content Analysis model, the research was conducted on August 15-15 September 2022 at Awal Bros Panam Hospital. There were 5 informants in the. The results showed that there were no SOPs and books on the use of PPE in the IPSRS room, there were still IPSRS officers who did not use PPE in accordance with the SOP at work, there was still a lack of special training on the use of PPE, and there were no facilities for training outside the hospital. It can be concluded that the compliance of officers in using PPE at IPSRS has not been entirely compliant. It is recommended that there are SOPs and books regarding the use of PPE that are displayed in the IPSRS room, strict sanctions are given to officers who do not wear PPE at work, additional special training on the use of PPE is carried out, facilitating unit heads to conduct training outside the hospital. Keywords: Compliance, Officer, Use PPE, IPSRS Literature: 34 (2012-2021)